Effect of feeding broilers with the diets containing leubim fish waste meals processed with including and without its skin on the weights and percentages of carcasses and internal organs of broilers - Zulfan Zulfan; Zulfikar Zulfikar; Herawati Latif; Nur Ismira Nyakdin; Galih Ajie Pangestu (Livestock and Animal Research, 2022)
Objective: This study aimed to evaluate the weights and percentages of carcasses and internal organs of broilers fed the partial substituted commercial ration (CCP) with leubim fish waste meal (LFW) made up of whole leubim fish waste meal (LFWW), leubim fish waste skin meal (LFWS), and skinless leubim fish meal (LFM‒S), each combined with yellow corn (YC) + top mix (TM).Methods: 100 broiler chicks strain CP 707 and commercial local fish meal (CFM) were employed in this study. The study was performed into a Completely Randomized Design with subsampling comprising 5 treatments, 4 replications, and 2 subsamples. The treatment was 100% CCP (control+) and 16.5% of substituted feeds composted of the CFM (control-), the LFWW, the LFWS, the LFM‒S, with the same level of 8% each + 8% YC + 0.5% TM each. The data were analyzed by Analysis of Variance.Results: Statistically, no significant differences (P>0.05) but substitute partial commercial diet with the mixture feeds constituted of LFW meals in the forms of LFWW, LFWS, LFW‒S, each added with   YC + TM had relatively higher weights of whole carcasses and cut-ups of broilers. Relatively to life weight, the carcass percentages were equal but the percentages of breasts significantly higher (P<0.05) in the broilers fed the LFW-based rations. There were no significant effects (P>0.05) on the weights and percentages of all internal organs.Conclusions: Substitute partial commercial ration with the leubim fish waste meal increased breast percentage without adverse effect on internal organs of broilers.